Omission of carbohydrate-rich breakfast impairs evening 2000-m rowing time trial performance - Cornford, E.; Metcalfe, R. (European Journal of Sport Science, 2019)
Purpose: The effect of breakfast omission on evening high-intensity exercise performance has not previously been studied. Methods: In a randomised and counterbalanced cross-over design, 10 competitive rowers (2 male, 8 female; mean ± SD: age 21 ± 2 y, height 176 ± 7 cm, weight 76 ± 12 kg, body fat 19.7 ± 6.8%) completed two trials (individualised carbohydrate-rich breakfast (BT; 831 ± 67 kcal eaten before 09:00) and no-breakfast (NBT; extended overnight fast until 12:00)). Following ad libitum afternoon food intake, participants completed a 2000-m time-trial on a rowing ergometer between 16:30 and 18:00. Appetite and energy intake were measured throughout the day, whilst power output, time, heart rate, blood lactate, blood glucose and RPE were assessed during the time trial. Results: Appetite ratings were higher throughout the morning in NBT compared with BT, but there were no differences in ratings in the afternoon. Energy intake at lunch was greater NBT compared with BT (1236 ± 594 vs 836 ± 303 kcal, p < .05), which partly compensated for breakfast omission, although overall energy intake tended to be lower in NBT compared with BT (1236 ± 594 vs 1589 ± 225 kcal, p = .08). The time taken to complete the 2000-m time trial was greater in NBT compared with BT (469.2 ± 43.4 vs 465.7 ± 43.3 s; p < .05). No differences in heart rate, blood glucose and blood lactate responses were apparent, but overall RPE was higher in NBT compared with BT (17.8 ± 0.9 vs 16.7 ± 0.7 au, p < .05). Conclusion: The omission of a carbohydrate-rich breakfast impaired evening performance during a 2000-m rowing time trial. This finding has implications for optimising evening high-intensity exercise performance.